2010
DOI: 10.1126/science.1191127
|View full text |Cite
|
Sign up to set email alerts
|

A Red-Shifted Chlorophyll

Abstract: Chlorophylls are essential for light-harvesting and energy transduction in photosynthesis. Four chemically distinct varieties have been known for the past 60 years. Here we report isolation of a fifth, which we designate chlorophyll f. Its in vitro absorption (706 nanometers) and fluorescence (722 nanometers) maxima are red-shifted compared to all other chlorophylls from oxygenic phototrophs. On the basis of the optical, mass, and nuclear magnetic resonance spectra, we propose that chlorophyll f is [2-formyl]-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
351
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 468 publications
(361 citation statements)
references
References 12 publications
5
351
0
5
Order By: Relevance
“…Furthermore, Chl f was recently discovered in filamentous (Chen et al, 2010;Airs et al, 2014;Gan et al, 2014) and unicellular cyanobacteria (Miyashita et al, 2014), enabling light harvesting even further into the NIR region up to B740 nm, often aided by employing additional far-red light-absorbing pigments such as Chl d and phycobiliproteins (Gan et al, 2014). Whereas the biochemical structure (Willows et al, 2013) and biophysical properties Tomo et al, 2014) of Chl f have been studied in detail, the actual importance of this new chlorophyll for photosynthesis is hardly explored (Li et al, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Chl f was recently discovered in filamentous (Chen et al, 2010;Airs et al, 2014;Gan et al, 2014) and unicellular cyanobacteria (Miyashita et al, 2014), enabling light harvesting even further into the NIR region up to B740 nm, often aided by employing additional far-red light-absorbing pigments such as Chl d and phycobiliproteins (Gan et al, 2014). Whereas the biochemical structure (Willows et al, 2013) and biophysical properties Tomo et al, 2014) of Chl f have been studied in detail, the actual importance of this new chlorophyll for photosynthesis is hardly explored (Li et al, 2014).…”
mentioning
confidence: 99%
“…In addition, weak spectral signatures of carotenoids and phycobilins, with absorption occurring at B495 and 665 nm, were evident in the hyperspectral data. Cyanobacteria, including those producing Chl d/f, are known to actively remodel their pigment content in response to the available light spectrum (Stomp et al, 2007;Chen and Scheer, 2013;Gan et al, 2014) and Chl d/f has almost exclusively been found in cyanobacteria grown under far-red light and not under visible light (Kü hl et al, 2005;Chen et al, 2010;Airs et al, 2014;Gan et al, 2014;Li et al, 2014;Miyashita et al, 2014). Recent work describes this acclimation response as 'Far-Red Light photoacclimation' (FaRLiP), which, in strain JSC-1, comprises a global change in gene expression and structural remodeling of the PSII/PSI core proteins and phycobilisome constituents (Gan et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely do extant oxygenic organisms possess chlorophylls with a longer wavelength range to ca. 720 nm, e.g., Chl d (Allakhverdiev et al 2010) and even Chl f (Chen et al 2010). Are these rare chlorophylls to be regarded as evolutionary remnants, as evolutionary transitions, or as interesting variants that do not represent direct clues to or from a major evolutionary path?…”
Section: Two Photosystems and The Water Splitting Complexmentioning
confidence: 99%
“…Such extension is possible using Chl d or f (Allakhverdiev et al, 2010, ;Chen et al, 2010;Chen and Blankenship, 2011;Chen and Scheer, 2013;Loughlin et al, 2013;Tomo et al, 2011Tomo et al, , 2014. However, the creation of artificial solar cells based on these chlorophylls is still in its early stages of development.…”
Section: Extension Of the Spectral Range Of The Light Absorption By Pmentioning
confidence: 99%